PERAN GURU PAI DALAM MENINGKATKAN GERAKAN BUDAYA LITERASI SEKOLAH PESERTA DIDIK DI SMKN 14 BANDUNG - Lutfiah Fatmah Sujanto; Zaki Kurniawan; Abdul Holik (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2022)
This study aims to plan to increase the extent of the role of Islamic Religious Education (PAI) teachers and how to increase the cultural literacy movement in schools. This is due to the low level of students' reading literacy culture in the form of a lack of students not using the school library. Even though the role of the school library is also very important to enhance the school literacy culture movement for students. This research method uses interviews (interviews) with several students and several PAI teachers in improving the school literacy culture movement. The results of this study indicate that the efforts made by PAI teachers are still minimal for students to carry out literacy culture movements in schools. So that shared awareness in terms of increasing the cultural literacy movement is very important for the future